(untitled) - LaBarge, Ralph (Lawrence, 2001)
Save time and money with the latest tools and techniques for publishing content in DVD formats. This comprehensive guide reveals everything you need to publish content in DVD-Video, DVD-ROM, and WebDVD formats - from project conception to replication and distribution.
Keywords: Multimedia systems,Hệ thống đa phương tiện